Pre- and Postoperative Gait Analysis and Video for Selective Dorsal Rhizotomy in Spastic Diplegia: 2-Dimensional Operative Video. Issue 3 (27th December 2018) - Archer, Jacob; Yaacoub, Alan P; Angulo-Parker, Francisco; Fritsch, Gloria; Riner, Shana; Coon, Ann; Johnson, Sarah K; Delima, Sarah; Jea, Andrew; Raskin, Jeffrey S
Abstract: Severe lower limb spasticity can hinder motor tasks and negatively impacts the quality of life in patients with cerebral palsy. Selective dorsal rhizotomy is a well-established neurosurgical intervention aimed at reducing muscle spasticity in patients with such neuromuscular conditions. Long-term outcomes of selective dorsal rhizotomy have been promising among the authors' institutional series of patients. In this case, we demonstrate the use of L1-S1 osteoplastic laminoplasty and L1-S1 selective dorsal rhizotomy in a 5-year-old male patient with cerebral palsy and spastic lower extremity diplegia. Favorable selection criteria for this case included disabling lower extremity diplegia, young age, good core strength, no cognitive delay, and strong rehabilitation potential. The patient's preoperative functional status was noncommunity ambulator (Gross Motor Function Classification System Level III) with walker use and good dynamic balance. Prior to the procedure, he demonstrated an overall decreased muscle strength in bilateral lower extremities with bilateral hamstring spasticity (Ashworth 3) and bilateral heel cord spasticity (Ashworth 4). Rhizotomy was performed with identification and selective sectioning of dorsal nerve roots with abnormal stimulation patterns. Fibers with unsustained discharge of appropriate muscles were identified and spared. No intraoperative or postoperative complications were encountered. The patient had minimal back pain and surgical morbidity postoperatively. Following the procedure and highly structured inpatient and outpatient rehabilitation therapies, the patient exhibited significant improvement in gait velocity (84%) and gait cadence (66%) at 5 months. Additionally, the patient demonstrated greater independence of activities of daily living and improvements in mobility by Pediatric Evaluation Disability Index. Patient consent was obtained from the parent.